A CONCEPTUAL MODEL AND PROCESS MANAGEMENT METHOD OF THE PLANNING AND MONITORING OF THE WORKLOAD IN THE EDUCATIONAL ENVIRONMENT - Biloshchytska, S.; Biloshchytskyi, A.; Omirbayev, S.; Mukhatayev, A.; Faizullin, A.; Kassenov, Kh. (Scientific Journal of Astana IT University, 2021)
The article formulates the aims of HEI’s activities, as well as approaches to managing all actions that ensure the achievement of the stated aims. The process approach is defined as the main one in the university management system. It is shown that the main directions of improving the activities of the university are the transition to the application of the process approach to the management of HEI and its informatization. On this basis, it is necessary to develop new, more modern university management systems that meet the contemporary requirements for the governance of multifunctional facilities and implement them in the form of process systems. We propose a conceptual model of the implementation of the functions to plan the educational process. The effects on planning functions are presented and the interrelation of these functions in the traditional form of planning is described. The tasks are formulated that need to be solved for modeling and optimizing business processes of planning and monitoring the academic workload to create an effective information technology for automating the functions of information processing. We propose a structural model for the implementation of information and procedural components of IT for planning and monitoring the educational environment. The implementation of this model in software provides the calculation of the optimal planned workload of students and teachers, considering the conditions in which the educational process is implemented.